Imagination and Creativity as Cultural Values: Dynamics of Societal Attitudes in Lithuania - Savicka, Aida (Sociologija. Mintis ir veiksmas, 2023)
Imagination and creativity are emerging as human qualities that are seen as essential to finding new solutions to the challenges of the contemporary world. Recognizing that creativity is not only an individual, but also a communal trait, there is an increasing focus on creating a cultural and social environment that is conducive to creativity, where playfulness and imagination are valued, where freedom of expression is encouraged, and where openness to diversity and a tolerance for risk-taking and failure prevail. One of the fundamental elements of such an environment is the common societal perception that imagination is an important part of human activity. Using the data of the European Values Study, this article analyzes the attitude of Lithuanian society towards the importance of fostering of imagination, its socio-demographic differences and the dynamics of this attitude in 1990–2017.
Keywords: imagination; creativity; creative class; European Values Study